Metabarcoding Analyses and Seasonality of the Zooplankton Community at BATS - Blanco-Bercial, Leocadio (Frontiers in Marine Science, 2020)
The diversity and specific composition of zooplankton communities have a direct effect on the ecosystem services (e.g. carbon export) and structure of ocean food webs. In areas where diversity is high, a detailed characterization of the whole community can represent a hurdle that prevents a complete understanding of those processes and interactions. One such region is the Sargasso Sea, where zooplankton diversity is among the highest in the world oceans. As a consequence, at the Bermuda Atlantic Time-series Study location, most research has focused on zooplankton biomass or on particular groups. To provide new insight into the total community composition at the BATS site, in this study the zooplankton community is investigated by means of metabarcoding of the 18S V9 hypervariable region. Day and night samples from a full year (2015) show the signature of diel vertical migration, driven by those groups with a higher representation in the metabarcoding reads. Seasonal ordination was detected after square-root transformation and, similarly to temperate regions, four seasons could be differentiated based on community composition (post-spring bloom, summer stratification, fall mixing event and winter mixing), with no correspondence with the zooplankton biomass patterns. This community ordination showed correlation with the measured vertical flux, highlighting the need of understanding community regimes, even in theoretically stable regions such as the oligotrophic ocean, to advance in our understanding of zooplankton-mediated processes